1999
DOI: 10.1007/bf03172966
|View full text |Cite
|
Sign up to set email alerts
|

Static and animated graphics in learning from interactive texts

Abstract: u.s.Animating the graphics in electronic documents may increase readers' willingness to study them but may impair or distort the processes of gist comprehension. Experiment 1 confirmed that, compared with static diagrams, animation increased readers' willingness to study a range of graphic genres (maps, time-lines, drawings of unfamiliar objects). Total reading time was also increased but readers' differential access of static and animated graphics confounded the interpretation ofimmediate and delayed retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…Wiley (2003) demonstrated that presenting images before a text reduced the negative impact of seductive imagery, while still increasing levels of interest for readers of history texts. In a parallel study, Wright, Milroy, and Lickorish (1999) found that presenting animation before a text also reduced any detriment to performance, when compared with embedded animation within a text. If poor comprehension were simply due to the reader's being given an inappropriate schema, presenting images beforehand should lead to equally poor, if not worse, learning outcomes.…”
Section: What Are Possible Explanations For the Seductive Details Effmentioning
confidence: 97%
“…Wiley (2003) demonstrated that presenting images before a text reduced the negative impact of seductive imagery, while still increasing levels of interest for readers of history texts. In a parallel study, Wright, Milroy, and Lickorish (1999) found that presenting animation before a text also reduced any detriment to performance, when compared with embedded animation within a text. If poor comprehension were simply due to the reader's being given an inappropriate schema, presenting images beforehand should lead to equally poor, if not worse, learning outcomes.…”
Section: What Are Possible Explanations For the Seductive Details Effmentioning
confidence: 97%
“…tables (Lemke 1998). These representational formats are also commonly found on digital 38 formats (Wright et al 1999 links between row and column and (6) the capacity to make the absence of a relationship 82 explicit.…”
mentioning
confidence: 99%
“…Although Harp and Mayer (1998) had proposed that the diversion hypothesis was the most likely explanation for seductive details affecting the learning process, Wiley (2003) demonstrated that presenting images before a text reduced the negative impact of seductive imagery. Wright, Milroy, and Lickorish (1999) found that presenting animation before a text also reduced any detrimental effect to learning performance, when compared with embedded animation within a text.…”
Section: Literature Reviewmentioning
confidence: 89%